“Umm you know…” Speaking or Writing?: Examining EFL Students’ Writing Style in Argumentative Essays - Setyaningsih, Nina; Larassati, Anisa (Elsya : Journal of English Language Studies, 2021)
Writing in English has always been a difficult skill to be mastered by Indonesian students. In the English Department of Universitas Dian Nuswantoro, students often face challenges in writing concerning grammatical rules and using suitable style in various text types. This research is aimed at investigating whether the students have applied formal academic style in their academic argumentative essays. The method used to analyse the data was descriptive qualitative. The findings demonstrate that there are still some significant errors made by students in their writing. Of the nine types of academic writing style errors proposed by Yakhontova (2003), there are eight types found in the data. These include contraction, addressing the reader directly, direct question, adverb in initial or final position, interjection and hesitation filler, short form of the word or slang, inappropriate negative form, and figures at the beginning of the sentence. Furthermore, the data also reveal a novel finding that there are two other kinds of error that cannot be categorised under Yakhontova’s framework, namely the use of spoken form and emoticon. This research suggests that students’ need to be specifically taught the differences between formal and informal styles of language in speaking and writing classes. They also need to be exposed to English academic texts more so as to be accustomed to formal or academic style.